2009
DOI: 10.3945/jn.108.103861
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-Linolenic Acid, EPA, and DHA Have Differential Effects on LDL Fatty Acid Composition but Similar Effects on Serum Lipid Profiles in Normolipidemic Humans

Abstract: Our aim was to study the effects of increased dietary intake of alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), or docosahexaenoic acid (DHA) on serum lipids and LDL fatty acid compositions. To this end, a controlled parallel study was conducted in 74 healthy normolipidemic men and women aged 19-43 y. Participants were randomly assigned to 1 of 3 interventions and consumed a total intake of 4.4 g/d ALA (ALA group), 2.2 g/d EPA (EPA group), and 2.3 g/d DHA (DHA group) for 6 wk. Fatty acid ethyl esters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
121
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 46 publications
10
121
4
2
Order By: Relevance
“…The subjects consumed margarines providing either 4.4 g of ALA, or 2.2 g of EPA or 2.3 g of DHA ethyl ester daily for 6 weeks. The study confirmed the TAG lowering effect of EPA (15% lower) and DHA (30% lower) and reported a 15% reduction in fasting serum TAG in the ALA group [140]. Patenaude et al compared the effect of increased consumption of ALA, from flaxseed oil (6 g/d for 4 weeks), in two age groups and reported a 20% decrease in circulating TAG concentration in younger subjects (18-29 y) compared to a 3.5% increase in older subjects (45-69 y) [144].…”
Section: Alpha-linolenic and Stearidonic Acids And Cardiovascular Rissupporting
confidence: 71%
See 2 more Smart Citations
“…The subjects consumed margarines providing either 4.4 g of ALA, or 2.2 g of EPA or 2.3 g of DHA ethyl ester daily for 6 weeks. The study confirmed the TAG lowering effect of EPA (15% lower) and DHA (30% lower) and reported a 15% reduction in fasting serum TAG in the ALA group [140]. Patenaude et al compared the effect of increased consumption of ALA, from flaxseed oil (6 g/d for 4 weeks), in two age groups and reported a 20% decrease in circulating TAG concentration in younger subjects (18-29 y) compared to a 3.5% increase in older subjects (45-69 y) [144].…”
Section: Alpha-linolenic and Stearidonic Acids And Cardiovascular Rissupporting
confidence: 71%
“…The reported effects of ALA on fasting TAG concentrations are also inconsistent; although a number of studies report a decrease [107,134,140,144,146,160,233,243,244], the majority (31 out of 40) report no effect (Table 9). There is consistent evidence that EPA and DHA lower blood TAG concentrations [186,246,247].…”
Section: Alpha-linolenic and Stearidonic Acids And Cardiovascular Rismentioning
confidence: 96%
See 1 more Smart Citation
“…The hypotriglyceridaemic effect of long chain n-3 PUFAs, mediated by several mechanisms such as enhanced hepatic fatty acid oxidation [69], inhibition of fatty acid and triglyceride synthesis, reduced assembly and secretion of VLDL triglyceride concentrations [70], facilitates triglyceride rich lipoprotein removal through enhanced LPL activity in plasma [71]. Significant increases in HDL have been observed after DHA supplementation [67,68,72,73]; it may be related to decreased cholesteryl ester transfer protein activity that reduces the exchange from HDL cholesterol ester and VLDL, resulting in larger, more cholesterol-rich HDL cholesterol particles [74,75].…”
Section: N-3 Polyunsaturated Fatty Acidsmentioning
confidence: 98%
“…Compares EPA and DHA, EPA-ethyl ester shows no change in triglyceride concentrations, suggesting that DHA is the active agent in fish oil, that decreases triglyceride concentrations. Therefore among long chain n-3 PUFAs, EPA may produce favourable effects on triglyceride and HDL cholesterol concentrations [67,68]. The hypotriglyceridaemic effect of long chain n-3 PUFAs, mediated by several mechanisms such as enhanced hepatic fatty acid oxidation [69], inhibition of fatty acid and triglyceride synthesis, reduced assembly and secretion of VLDL triglyceride concentrations [70], facilitates triglyceride rich lipoprotein removal through enhanced LPL activity in plasma [71].…”
Section: N-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%